Understanding modern dive computers and operation : protocols, models, tests, data, risk and applications - Wienke, B. R.; O'Leary, T. R. (Cham, Switzerland : Springer, 2018)
This brief provides a complete yet concise description of modern dive computers and their operations to date in one source with coupled applications for added understanding. Basic diving principles are detailed with practical computer implementations. Interrelated topics to diving protocols and operational procedures are included. Tests, statistics and correlations of computer models with data are underscored. The exposition also links phase mechanics to dissolved gases in modern decompression theory with mathematical relationships and equations used in dive computer synthesis. Applications focus upon and mimic dive computer operations within model implementations for added understanding. This comprehensive resource includes a complete list of dive computers that are marketed and their staging models, as well as a complete list of diveware marketed and their staging algorithms, linkage of pertinent wet and dry tests to modern computer algorithms, a description of two basic computer models with all constants and parameters, mathematical ansatz of on-the-fly risk for surfacing at any dive depth, detailing of statistical techniques used to validate dive computers from data, and a description of profile Data Banks for computer dive model correlations. The book will find an audience amongst computer scientists, doctors, underwater researchers, engineers, physical and biosciences diving professionals, explorers, chamber technicians, physiologists and technical and recreational divers.
Computer Vendor and Training Agency DCS PollTraining Agency Testing and Standards; References; Risk Estimators; End of Dive Risk Estimator (EOD); Test Profiles and EOD Risk; On the Fly Risk Estimator (OTF); Test Profiles and OTF Risk; Equal Risk Deep and Shallow Stop Profiles; References; Computer Diveware; Packages; Examples; Rebreather and Open Circuit Profiles; Diveware Model Characteristics Comparison; Comparative GM and BM Risk Estimates for Wet Pod Trials; References; Bubble Issues and Dive Computer Implementations; Bubble Dynamics; Bubble Regeneration; Bubble Broadening; References.
Online resource; title from digital title page (viewed on October 08, 2018).
Keywords: Dive computers; TECHNOLOGY & ENGINEERING -- Hydraulics; Software Engineering; Reliability engineering; Biophysics; Sports & outdoor recreation; Expert systems -- knowledge-based systems; Dive computers; Electronic books